Factoring and Cash Discount as methods for optimizing the Net Working Capital : Case Study - Heinonen, Antti (My University, 2021)
The COVID-19 and raising interest rates will affect on companies’ capital costs and cash flows which make a working capital management more critical. For being able to save costs, the more efficient ways to manage working capital in accounts receivable and payable and inventories are needed. This thesis aims to shed light on the working capital management tools on sale side. In the thesis the basic theories of the working capital management are first presented. The most common ways for inventory management are EOQ and JIT theories. In accounts receivables and payables management the maximizing and minimizing the payment times are emphasized. On sale side the most used options are the usage of cash discounts or factoring. Cash discount means an action where the certain discount percentage is given to a customer if the customer pays earlier. We present the different theories for defining the optimal cash discount policy. In factoring the invoices are sold to a factor for getting the immediate payment. The factoring can be divided into recourse and non-recourse option depending on the risk. We present the basic profit and pricing theories of both options. In the analyzing part we simulate both methods by using the case company’s data. We define the optimal cash discount and factoring policies and simulate them by data of one fiscal year. The figures are presented. We then compare, how the methods effect on the net working capital level and profitability. It seems obvious that in theory the most efficient way is cash discount, but we admit that, because the choice of the usage is done by a customer, the result can vary. Factoring is more predictable, but the costs of automatic factoring are much higher, and the results are not that significant compared to the cash discount option. Therefore, the most certain and best way to handle the net working capital is manual non-recourse factoring. For further studies the more case studies in different industries are needed because the results themselves may vary between the companies and industries and are not generalized.

Koronapandemia sekä nousevat korot vaikuttavat vahvasti yritysten pääomakustannuksiin ja kassavirtaan, jonka johdosta käyttöpääoman hallinta on yhä tärkeämpää. Tehokas käyttöpääoman hallinta korostuu varastoinnin sekä osto- ja myyntisaamisten hallinnoinneissa, jotta pääomakustannusten säästöjä saadaan aikaan. Tämän tutkielman tarkoituksena on tutkia eri metodeja osana myyntipuolen käyttöpääoman hallintaa. Tutkielmassa esitellään käyttöpääoman hallinnan perusteorioita aihealueittain. Varastoinninhallinnan tärkeimmät teoriat ovat EOQ- sekä JIT-teoriat. Osto- ja myyntisaatavien hallinnassa korostuu maksuajan minimointi tai maksimointi. Myyntipuolella tutkitaan käteisalennuksen käytön sekä factoring-rahoituksen käytön vaikutusta käyttöpääomaan. Käteisalennus tarkoittaa alennusta, joka myönnetään asiakkaalle, mikäli tämä maksaa ennen laskun varsinaista eräpäivää. Factoring-rahoituksessa taas ostosaaminen myydään välitöntä maksua vastaan rahoituslaitokselle. Factoring-rahoitus voidaan jakaa riskilliseen tai riskittömään rahoitusmuotoon. Tutkielmassa esitetään molempien muotojen perusansainta- sekä hinnoitteluteorioita. Analyysiosiossa molempia metodeja simuloidaan käyttämällä case-yrityksen dataa. Optimit mallit käteisalennukselle sekä factoring-rahoitukselle määritellään, jonka jälkeen ne simuloidaan yhden tilivuoden datalla. Tämän jälkeen tuloksia vertaillaan keskenään. Selvästi parhaaksi metodiksi tulosten varjossa nousee käteisalennus, mutta voidaan todeta, että käytännössä sen käyttöönotto riippuu asiakkaasta, joten tulos on ainoastaan teoreettinen. Factoring-rahoitus on ennustettavampi, mutta erityisesti automaattisen factoring-rahoituksen kulut ovat käteisalennukseen verrattuna kovat, eivätkä tulokset ole niin merkittävät. Tämän johdosta manuaalinen factoring-rahoitus on paras ja luotettavin vaihtoehto käyttöpääoman hallintaan. Tulevissa tutkimuksissa tarvitaan lisää case-tutkimusta molemmista metodeista, sillä vaikkakin metodologia voidaan monistaa muihin yrityksiin, eivät tulokset itsessään ole yleistettävissä.
Keywords: working capital management, cash discount, factoring